2019
DOI: 10.1088/1361-665x/ab1acb
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional constitutive model for the martensitic transformation in polycrystalline shape memory alloys under large deformation

Abstract: This work presents a three-dimensional constitutive model for the martensitic transformation in polycrystalline Shape Memory Alloys (SMAs) under large deformation. By utilizing the logarithmic strain and rate, the model is able to account for large strains and rotations that SMA-based components may undertake, but also resolves the artificial stress errors caused by the non-integrable objective rates that are widely used in current commercial finite element software. The model is developed through classical th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…However, the underlying microscale physical mechanisms of SMA behavior are not reflected in macroscale phenomenological constitutive models. Representative macroscopic SMA models include Auricchio et al (2007), Lagoudas et al (2012), Panico and Brinson (2007), Zaki and Moumni (2007), Arghavani et al (2010), and Xu et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the underlying microscale physical mechanisms of SMA behavior are not reflected in macroscale phenomenological constitutive models. Representative macroscopic SMA models include Auricchio et al (2007), Lagoudas et al (2012), Panico and Brinson (2007), Zaki and Moumni (2007), Arghavani et al (2010), and Xu et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…There has been a lot of constitutive modeling efforts been made during recent decades to predict the intrinsic material response of SMAs, a through review can be found from elsewhere. [24][25][26][27] As the motivation of this research is to facilitate the development of a phenomenological model that is able to capture the tensioncompression asymmetry and TRIP during cyclic thermo-mechanical actuation loading, the results obtained from previously performed tension/compression and bending experiments are used for the formulation and validation of the SMA constitutive model capturing the anisotropic phase transformation characteristics. In order to achieve the desired modeling capability, modifications on the transformation functions are needed.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…It is worthy to point out that the input variables used for this implementation collected from the global finite element solver are the temperatures (T n , T n+1 ), and deformation gradients at the current and next step (F n , F n+1 ). As it was discussed in the work of Xu et al (2019a), such non-trivial considerations on the kinematics allow for the implementation of the model to get rid of the accumulated stress errors as a result of using other non-integrable objective rates. The effects of such accumulated stress errors on the cyclic thermomechanical response of SMAs are analyzed in detail from Xu et al (2019a).…”
Section: Methodsmentioning
confidence: 99%
“…As it was discussed in the work of Xu et al (2019a), such non-trivial considerations on the kinematics allow for the implementation of the model to get rid of the accumulated stress errors as a result of using other non-integrable objective rates. The effects of such accumulated stress errors on the cyclic thermomechanical response of SMAs are analyzed in detail from Xu et al (2019a).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation